PSYCHOLOGICAL PECULIARITIES OF THE USE OF SLANG AMONG YOUNG PEOPLE AND EDUCATORS - Sheralieva M.S. (Western European Studies, 2024)
This article will address the problems related to the use of slang in youth circles, the reasons why slang is used in speech, as well as a description and brief etymology of this word. The peculiarity of this scientific work is that it examines the issue of combating such a linguistic phenomenon as slang
Keywords: youth slang; professional slang; psychological protection